Treatment of cervical contractures utilising a closed platysmotomy like approach: Case report and review of the literature. Issue 6 (September 2016) - Haik, Josef; Prat, Daphna; Kornhaber, Rachel; Tessone, Ariel
Highlights: Post-burn cervical contractures cause restrictions in range of movement. A closed platysmotomy like approach is a less invasive technique for cervical contractures. Aesthetic and functional results can be achieved with minimally if any residual scarring. Abstract: Contractures to the cervical region as a result of burns has the capacity to cause restrictions in range of movement, function of the lower face, cervical spine distortion and poor aesthetic outcomes that remain a surgical challenge. Consequently, physical and aesthetic deformities as a result of cervical contractures are reported to cause depression having implications for patients' quality of life and psychosocial wellbeing. At the time this research was conducted, there were no case reports describing a closed platysmotomy approach in burn patients. In this article, we review the literature surrounding closed platysmotomies and present what we believe to be the first reported case in the treatment of cervical contractures utilising a closed platysmotomy approach in a burns patient. A closed platysmotomy approach for the treatment of cervical contractures is a less invasive technique. Further investigation is warranted to determine the feasibility of this reconstructive approach in the area of burn scar management.